Cooperative-Collaborative Learning in Enhancing Creative Writing Performance - Acuin, Dandy G.; Petallana, Mona Lisa D.; Esperas, Geraldine C. (JPAIR Multidisciplinary Research, 2018)
Writing is among the communication skills covered in both Filipino and English language teaching that every learner should develop at any level of education in the Philippines. However, teaching creative writing skills continues to be a very challenging task for teachers. It is a challenge, therefore, for teachers to motivate students to write. More so, it is a challenge for students to write creatively. Using the action research design, this study aimed to test and examine the effectiveness of cooperative-collaborative learning using the specific strategy, Team Pair Solo, in enhancing their creative writing skills. Triangulation is also used in this study to examine, verify, and cross-check the data at different angles such as observation, analysis of the pre and post writing composition, and from the interviews of the students. The finding shows positive effects of cooperative-collaborative learning in enhancing creative writing performance among the students. It is recommended that cooperative-collaborative learning strategy (Team Pair Solo) should be used in teaching to enhance the creative writing skills of students. It is further recommended that other cooperative-collaborative learning strategies be studied for the same purpose.
Keywords: Cooperative-Collaborative Learning; creative writing; action research design; learning styles; strategies and outcome; Philippines